Industrial training report: JKR Segamat Johor / Muhammad Kamil Jusoh - Jusoh, Muhammad Kamil (Bachelor of Information Science (Hons.) Records Management, 2015)
Records contain information which could determine the success or failure of an organisation. Paradoxically, organisations do not prioritise the implementation of such initiative so much so no policy is legislated to guide the direction in managing such strategic source of information. But records ought to be managed efficiently to improve the quality of service delivery which then enhances the competency of organisation. This strategic source of information needs to be effectively managed to improve the quality of service. This paper seeks to investigates the implementation of records management initiative in the Public Works Department of Malaysia (PWD), the largest teknikal department in the nation. The study focuses on records management using ICT applications with the objective to identify level of awareness pertaining to records management policy, to identify level of procedure acceptance pertaining to records management using ICT applications, investigate level of ICT usage for managing records, and to identify relationship between policy, procedure and use of ICT application in the PWD of Malaysia.